2016
DOI: 10.3171/2016.5.peds16115
|View full text |Cite
|
Sign up to set email alerts
|

Rapid de novo aneurysm formation after clipping of a ruptured middle cerebral artery aneurysm in an infant with an MYH11 mutation

Abstract: The authors report the case of a previously healthy 6-month-old girl who presented with right arm and leg stiffening consistent with seizure activity. An initial CT scan of the head demonstrated acute subarachnoid hemorrhage in the basal cisterns extending into the left sylvian fissure. Computed tomography angiography demonstrated a 7 × 6 × 5–mm saccular aneurysm of the inferior M2 division of the left middle cerebral artery. The patient underwent left craniotomy and microsurgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…D E www.the-jcen.org ally thought to be due to arterial wall weakening and/or the influence of hemodynamics stress. [11][12][13][14] Similarly, our hypothesis is that a change of focal hemodynamic stress by microsurgical clipping may be one of the main factors that leads to decreasing resistibility and structural fra- unsuccessful clipping are associated with aneurysms located at the anterior communicating artery complex or posterior circulation. 6-9)12) However, MCA trunk aneurysms are located either on the main trunk, at the origin of an early frontal or temporal branch, or at the origin of the lateral LSA.…”
Section: Discussionmentioning
confidence: 94%
“…D E www.the-jcen.org ally thought to be due to arterial wall weakening and/or the influence of hemodynamics stress. [11][12][13][14] Similarly, our hypothesis is that a change of focal hemodynamic stress by microsurgical clipping may be one of the main factors that leads to decreasing resistibility and structural fra- unsuccessful clipping are associated with aneurysms located at the anterior communicating artery complex or posterior circulation. 6-9)12) However, MCA trunk aneurysms are located either on the main trunk, at the origin of an early frontal or temporal branch, or at the origin of the lateral LSA.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the MCM4 TF was shown to be at a high degree in the integrated network and was predicted to regulate the expression of MYH11 . Additionally, mutation of myosin heavy chain 11 ( MYH11 ) was inversely correlated with RIA ( 35 ), which suggested that the MCM4 TF regulates MYH11 for participating in the development of IA.…”
Section: Discussionmentioning
confidence: 99%
“…SMTN family are composed of SMTN-a, SMTN-band SMTNL1.SMTN was expressed in tunica media SMCs of normal arteries , but unexpressed in the media SMCs of saccular intracranial aneurysm (sIA); Meanwhile, sIA SMCs showed signi cant decrease of MYH11 expression 25 . It's reported that MYH11 mutation correlated with thoracic aortic aneurysms, dissections and de novo intracranial aneurysm formation 26 .TAGLN is an actin binding enzyme of the calponin family, performing actin binding and actin bundling activities. Loss of TAGLN promotes thoracic aortic aneurysm and aortic dissection progression in vivo 27 .…”
Section: Smcs Contractile Dysfuction (Dedifferentiation) Refers To the Degeneration From An Initial Contractilementioning
confidence: 99%